Development of Natural Sodium Montmorillonite as a Cathode Material - Goonathilake, W.K.O.W.; Bandaranayake, P.W.S.K. (University of Jaffna, 2022)
Montmorillonite (MMT) is naturally occurring clay mineral in Sri Lanka. It is an aluminosilicate crystalline compound with layered structure. In this structure an octahedral sheet of aluminum-oxygen (Al-O) is sandwiched between two tetrahedral sheets of silicon-oxygen (Si-O). The MMT structure can accommodate various monovalent and divalent cations such as H+, Li+, Na+, Mg2+ within the interlayer spacing. Natural Li-MMT and Na-MMT are found in various parts of the world. The MMT structure has an ability to exchange interlayer cations with various other divalent cations. MMT with interlayer alkali cations show appreciable ionic conductivity. Natural Na-MMT found in Sri Lanka was used for the present study. To improve the ionic conductivity of natural Na-MMT, the structure was further saturated with Na+ ions. The Na+ ion concentration of saturated Na-MMT was measured by Inductive Couple Plasma Mass Spectroscopy. The structural and electrical properties of Na saturated MMT were characterized by SEM and Complex Impedance Spectroscopy. As a result of Na+ ion saturation the bulk conductivity of Na-MMT was increased to 3.41×10-4 S cm-1 at 30 C . Saturated Na-MMT has negligible electronic conductivity which is less than 0.001%. For using Na-MMT as intercalation cathode materials in rechargeable batteries, an appreciable electronic conductivity must also be present. To enhance the electronic conductivity of saturated Na-MMT, carbon black was mixed. The electronic transference number of saturated Na-MMT pellets was measured by the DC polarization technique. The electronic transference number of saturated Na-MMT with 25% and 30% carbon black were 0.81 and 0.87 respectively.
Keywords: Cation exchange; Carbon black; Electrical conductivity; Intercalation cathode; Sodium montmorillonite